Fabrication of graphene field effect transistors on complex non-planar surfaces - Holicky,M; Fenech-Salerno,B; Cass,A; Torrisi,F (Applied Physics Letters, 2024)
Graphene field effect transistors (GFETs) are promising devices for biochemical sensing. Integrating GFETs ontocomplex non-planar surfaces could uncap their potential in emerging areas of wearable electronics, such as smartcontact lenses and microneedle sensing. However, the fabrication of GFETs on non-planar surfaces is challengingusing conventional lithography approaches. Here, we develop a combined spray coating and photolithography setupfor the scalable fabrication of GFETs on non-planar surfaces and demonstrate their application as integrated GFETs onmicroneedles. We optimize the setup to pattern 67 µm long GFET channels across the microneedle tips. Graphene isdeposited between photo-patterned electrodes by spray coating a liquid-phase exfoliated graphene ink, while monitoringthe channel resistance to achieve the required conductivity. The successful formation of the GFET channels is confirmedby SEM and EDX mapping, and the GFETs are shown to modulate in solution. This demonstrates an approach for themanufacturing of graphene electronic devices on complex non-planar surfaces like microneedles and opens possibilitiesfor wearable GFET microneedle sensors for real-time monitoring of biomarkers.